Pengaruh Teknik Pernapasan Buteyko terhadap ACT (ASTHMA CONTROL TEST) - Marlin Sutrisna; Emmy H Pranggono; Titis Kurniawan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to determine the effect of buteyko breathing technique on asthma control test (ACT).The quasi experimental study with the pretest and post test one group design approach involved 14 patients with asthma selected from the Lung Polyclinic of Dr. Hasan Sadikin Bandung with consecutive sampling. Asthma control was collected using time series ACT. The collected data were analyzed descriptively and inferentially with the scale of significance p <0.05.The results showed a significantly higher mean difference between ACT scores after buteyko breathing technique (19.79 ± 1.47) with ACT score at week III (17.50 ± 1.78), week II (12.64 ± 1.82), week I (9.57 ± 1.95), and pretest (7.64 ± 1.82). Post hoc analysis found the fourth week post test score (19.79 ± 1.47) significantly better than post test week III (17.50 ± 1.78), week II (12.64 ± 1.82), week I (9.57 ± 1.95), and pretest (7.64 ± 1.82) in improving asthma control. Conclusion, there was an effect of buteyko breathing technique on asthma control test (ACT). Keywords: ACT, Breathing Technique, Bronchial Asthma, Buteyko